THE EFFECT OF SOCIAL MEDIA MARKETING ON INSTAGRAM TOWARDS PURCHASE INTENTION & PURCHASE DECISION OF ERIGO PRODUCTS - Eugenia Clarissa Prabowo; Rita Komaladewi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The rapid growth of Instagram usage in Indonesia has transformed how brands connect with consumers, making it a vital platform for marketing and brand engagement. This shift is accompanied by an increase in online shopping behavior, accelerated by the post-pandemic environment, which has made consumers more comfortable with digital transactions and purchasing products online. Additionally, the high competition within the fashion industry has driven local brands to adopt innovative digital marketing strategies to stand out and attract consumers. Erigo, a leading local fashion brand, has effectively utilized Instagram to enhance brand visibility and engage directly with its target audience. This study aims to analyze the impact of Social Media Marketing (SMM) on Instagram on purchase intention and purchase decision for Erigo products. A quantitative approach was employed, gathering data from 210 respondents who have interacted with Erigo’s Instagram content. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was utilized to test the hypotheses. The analysis results indicate that SMM on Instagram significantly enhances both purchase intention and purchase decision, demonstrating the importance of engaging and interactive content in driving consumer behavior. These conclusions suggest that strategic use of Instagram not only increases consumer interest but also effectively drives actual purchases, highlighting the value of digital marketing strategies in maintaining competitiveness and fostering growth in Indonesia’s fashion market.